Impactos da discrepância entre o trabalho prescrito e real dos fiscais de contrato em universidades públicas federais - Matias, Érika Pena Bedin (2017)
This dissertation discusses the contract inspection service of federal public universities established in the state of São Paulo. Contract inspectors have the responsibility of ensuring compliance with administrative contracts concluded between outsourced companies and universities, through monitoring and inspection. In this context, the purpose of this study is to identify the impacts that the discrepancy between the prescribed and actual work causes to the contract inspectors. To do so, a qualitative research was used, based on a multicaso study delineated by the Activity Ergonomics, in which interviews were applied to fourteen employees from three universities. The results indicate the specificities and the difficulties of the work, investigating the discrepancies between the prescribed and actual work, as well as the impacts that are related to the physical environment, intellectual challenges imposed by the work, control of the emotions, pressures for compliance in the deadlines and administration of conflicts. It was possible to raise and analyze the risks of illness, as well as the strategies adopted to combat illness. However, as they occur individually, they do not lead to a change in the organization of work. With the help of the validation of the results it was possible to make some notes for improvements. In addition, the research points out possibilities to promote restructurings in the current organizational system in order to value human and behavioral development as a perspective in the creation, implantation and dissemination of organizational practices that reconcile productivity and the revitalization of the one who produces, increasing commitment and organizational links.